1991
DOI: 10.2307/2008411
|View full text |Cite
|
Sign up to set email alerts
|

Primitive t-Nomials (t = 3, 5) Over GF(2) Whose Degree is a Mersenne Exponent 44497

Abstract: All primitive trinomials over GF (2) with degree 859433 (which is the 33rd Mersenne exponent) are presented. They are X 859433 + X 288477 + 1 and its reciprocal. Also two examples of primitive pentanomials over GF (2) with degree 86243 (which is the 28th Mersenne exponent) are presented. The sieve used is briefly described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Although complete descriptions are not always given in the original papers, previous computations [9,10,12,14,20,21,24,26] involving irreducible or primitive trinomials seem to have used some variant of sieving combined with squaring and reduction, much as described above. This is why we call it the standard algorithm.…”
Section: Reduction Mod P (X) Reduction Of A(x)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although complete descriptions are not always given in the original papers, previous computations [9,10,12,14,20,21,24,26] involving irreducible or primitive trinomials seem to have used some variant of sieving combined with squaring and reduction, much as described above. This is why we call it the standard algorithm.…”
Section: Reduction Mod P (X) Reduction Of A(x)mentioning
confidence: 99%
“…Kurita and Matsumoto [14] extended the search to r ≤ 86243, and Heringa et al [10] to r ≤ 216091. Kumada et al [12] conducted an exhaustive search for r = 859433 and found one primitive trinomial.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are: to use pentanomials [Kurita and Matsumoto 1991], to combine trinomials [Tezuka and L'Ecuyer 1991;Wang and Compagner 1993], and to twist [Matsumoto and Kurita 1994]. It seems that, for these generators also, the behavior around the fixed vector would be worth testing.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The most common way is to use three-term linear recursion, in other words, to use primitive trinomials as characteristic polynomial. These primitive trinomials are intensively searched in Heringa et al [1992] and Kurita and Matsumoto [1991]. In this paper, however, we reveal a serious flaw of trinomial generators.…”
Section: Characteristic M-sequencementioning
confidence: 93%
“…The integers r listed in Table 1 are the known Mersenne exponents of the form r = ±1 mod 8 in the interval [100 000, 32 582 657]. For smaller exponents, omitted to save space, see [10] or our web site [1]. According to the GIMPS Project [7], the list is complete for r ≤ 16 300 000.…”
Section: Theorem 1 For the Integers R Listed Inmentioning
confidence: 99%